Dante in Giorgio Caproni’s poetry. - Härri, Silvia (Cuadernos de Filología Italiana, 2004)
In this article, we have made a fine analysis of a selection of Dante’s quotations in Giorgio Caproni’s Il muro della terra. We paid special attention to the verses of Dante, which were selected at some time as potential titles for the work. Firstly, we analysed an expression of Inferno (If. XVI, 91-93: «orgoglio e dismisura»), which is used by Caproni in the poem Via Pio Foà I. Secondly, we focused on a tercet of the canto of thieves (If. XXIV, 91-93: Tra questa cruda e tristissima copia / correan genti nude e spaventate, / sanza pertugio o elitropia), which is often quoted by the author, who explicitly mentions his source, whitout making connexions between his own poems and Dante’s intertext clear. Finally, through these textual points of convergence, we have tried to explore the link wich exists between the author and his favourite source and have elaborated some hypothesises on the different ways of quoting used by Caproni in his poetry.